(3OjhGf GdeJfHjs - (3CHh GdWjH, GdeJfHj, CMeO Hf GdMSjf Hf GdMSf, J(B354(3g`s
(3ChdgG (B:s
(3CHdi Gdghi BSaG jhe Gdfhi (B*** (3heRb GdgLQ Hjf GdLaf hGdhSf , QhM JQOO aj eKd GdNdGds
(3BNQgG (B:s
(3heG CfG ZjQ Sge aj ghGA (B*** (3jYhO hde JLO ajg edSG , MHj ef Edgj Cf jQGfj (B*** (3hbO aGQbJ OGQc hGUWaGcGs
(3jfJgj GdOjhGf YfO b(B211(3, hjdjg PcQ ebJd GdeJfHj hJQLeJg ef cJGH JGQjN GHf NdcGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 115s
(3eYLe GdeDdajf(B: 1 / 126s
(3cTa GdXfhf(B: 1 / 809s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs